Disparity in Birth Size of Ethiopian Preterm Infants in Comparison to International INTERGROWTH-21st Data - Netsanet Workneh Gidi MD; Robert L. Goldenberg MD; Assaye K. Nigussie MD; Zelalem Tazu Bonger MSc; Elizabeth M. McClure PhD; Mahlet Abayneh MD; Matthias Siebeck MD; Orsolya Genzel-Boroviczény MD; Lulu M. Muhe MD (SAGE Publishing, 2020)
Background . Patterns of fetal growth are largely influenced by environmental, nutritional, and socioeconomic factors more than differences in populations. The aim of this study was to assess anthropometric measurements of Ethiopian preterm infants at birth and compare the results with the international INTERGROWTH-21st data. Patients and methods. We analyzed anthropometric data on live-born singleton preterm infants enrolled in a hospital-based multicenter study of illness in preterm infants (SIP). Eligible newborns with gestational age of 28-36 weeks were included. Gestational age (GA) and sex-specific mean and standard deviations (SD), 10th, 50th, 90th, centile values for birth weight, length and head circumference (HC) were calculated and compared with INTERGROWTH-21st data. Result . A total of 2763 preterm infants were included in the study, 54% were male. The prevalence of small for GA (SGA) (<10th percentile) and large for GA (LGA) (>90th percentile) were 10.8% and 9.9%, respectively. In all 3 parameters, the mean values of boys were higher than of girls. Birth weight centiles were comparable to international averages at lower GA, then after GA of 32 weeks the 10th, 50th, and 90th centile values were 100-500 g less than the international averages. The head circumference centiles were mostly comparable, and the 90th centile values were greater than the international averages across the GA and in both sexes. Conclusion. The infants' birth weights were smaller at higher GA, which may indicate maternal undernutrition in the third trimester of pregnancy. Strengthening antenatal nutrition counseling and providing nutrition supplementation might improve the birth weight.